Cinnamon Roll murder - Fluke, Joanne (New York, NY : Kensington Books, 2013)
When Hannah Swensen hears that the Cinnamon Roll Six jazz band will be playing at a festival in Lake Eden, Minnesota, she bakes up a supply of their namesake confections to welcome them. But tragedy strikes when their tour bus overturns on its way into town. And keyboard player Buddy Neiman's minor injuries turn deadly serious when someone plunges surgical scissors into his chest. Turns out, Buddy Neiman isn't the victim's real name. In fact, no one is really sure who he is. Hannah's investigation digs up a few local suspects. There is Doctor Bev, who seems to know more about "Buddy" than she's willing to admit. And Devon, an aspiring keyboard player who may have had a fatal case of jealousy. Hannah isn't sure how she'll unravel the mystery, but one thing's for sure: there's nothing sweeter than bringing a killer to justice.
Includes recipe index.
Includes an excerpt from the author's Red velvet cupcake murder in back of book.
Keywords: Swensen, Hannah (Fictitious character); Bakers; Bakeries; Women private investigators -- Minnesota; Murder -- Investigation; Jazz musicians -- Crimes against; Minnesota; Mystery fiction